Massification of the individual and inauthenticity in dialogue - Andrade Mogrovejo, David Ricardo (2021)
The aim of this article is to analyze both the psychological and social problems involved in the conversion of the individual into a mass, and inauthentic dialogue. The psychological and social mechanisms that deprive an individual of their authenticity and merge them into the mass are presented, also emphasizing the difficulty of establishing an authentic dialogue with others because of the alienation of oneself and the identity conflict. Likewise, elements such as the loss of identity, education, authenticity, freedom, responsibility, conscience, and intentionality are considered, with the purpose of enriching the analysis of this problem. A bibliography based on authors such as Viktor Frankl, Ronald Laing, Rollo May, Soren Kierkegaard, José Ortega y  Gasset, Carl Rogers, Byung Chul Han, Zygmunt Bauman, Emmanuel Lévinas Miguel de Unamuno, Max Scheler, William Davies, Joan-Carles Mélich and Jean Paul Sartre was used as background for this study. As proposals and conclusions to face this problem, the article stresses the construction of a community where differences between individuals are accepted, and a more authentic dialogue between people is promoted through individual commitment and action.